Economic Empowerment Of Women In Kalideres Through Creative Home Industry Using Traditional Cakes - Yanti, Peby; Wahyunengsih (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2023)
Economic empowerment of women through the traditional cake-making home industry is an effective way to increase women's economic independence and promote traditional cultural heritage. This study aims to find out what strategies are used by home industries in making traditional cakes and in managing their business to maintain quality and the selling value of its products in the point market. In addition, this research also aims to improve the economy of these creative home industry players. The method used in this study is a qualitative method and observation in which the subject is the owner of this traditional cake-making home industry, as well as observations on where the creative home industry takes place. While the data that has been obtained and explained qualitatively and in the results of observations show that with training and development of business principles, traditional cake-making home industries can develop businesses that can improve the economy of the home industry players, most of whom are women.